Learning Management in Improving the Quality of Graduates at Job Training Institutions - Tatang Sutarjo; Waska Warta; Usep Suherman (At Turots: Jurnal Pendidikan Islam, 2025)
The phenomenon of the Open Unemployment Rate (OUR) data released at the national, provincial, and district levels remains a significant concern. One contributing factor is the low quality of the workforce required by the Business and Industrial World (DUDIKA). Therefore, there is a pressing need for Job Training Institutions (LPK) capable of producing high-quality graduates. The achievement of student quality in training institutions is largely determined by the institution's mastery of learning management. The purpose of this study is to describe and analyze learning management in improving the quality of graduates at LPK CTI Ciamis District and LPK CBI Kawali District, which can contribute to reducing the unemployment rate in Ciamis Regency. This study utilizes a descriptive qualitative research method. Data collection was conducted through observation, interviews, and documentation. The data analysis process employs an interactive model analysis consisting of data reduction, data presentation, and conclusion drawing. The framework relies on the management principles of Planning, Organizing, Actuating, and Controlling. The results indicate that: (1) Learning management at LPK CTI Ciamis District is functioning well. This is evidenced by learning plans based on the SKKNI Curriculum, Lesson Plans/Syllabi, and Session Plans (RPP); organized structures based on established Standard Operating Procedures (SOP); conducive learning implementation aligned with initial planning; and continuous supervision and evaluation until students are declared competent. (2) The graduate quality at LPK CTI Ciamis District has increased year by year, as seen from the number of high-achieving graduates successfully entering DUDIKA. In conclusion, efforts to produce quality graduates have been successful due to the implementation of excellent learning management.